2015
DOI: 10.1002/aur.1522
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical glutathione levels in adults with autism spectrum disorder

Abstract: Increased oxidative stress has been postulated to contribute to the pathogenesis of autism spectrum disorder (ASD). However, reports of alterations in oxidation markers including glutathione (GSH), the major endogenous antioxidant, are indirect, coming from blood plasma level measurements and postmortem studies. Therefore we used in-vivo 3 Tesla proton magnetic resonance spectroscopy ([1H]MRS) to directly measure GSH concentrations in the basal ganglia (BG) and the dorsomedial prefrontal cortex of 21 normally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…When compared to previous studies using PR-STEAM in healthy controls, the GSH levels or GSH/tCr levels are within the 95% confidence intervals of the levels reported. 13,14 Even though the voxel size and partial volume correction technique varied, the PRESS GSH levels reported here are similar to those in healthy volunteers in another study with the voxel placed in the ventral anterior cingulate, 2 and are slightly lower than the mean GSH levels from the dorsomedial prefrontal cortex in healthy controls 29 or from the left anterior cingulate in healthy controls. 21 When calculated relative to total creatine, GSH/tCr levels in this study were similar to or slightly higher than healthy control GSH/tCr levels measured using SPECIAL from the medial prefrontal cortex.…”
Section: Discussionsupporting
confidence: 74%
“…When compared to previous studies using PR-STEAM in healthy controls, the GSH levels or GSH/tCr levels are within the 95% confidence intervals of the levels reported. 13,14 Even though the voxel size and partial volume correction technique varied, the PRESS GSH levels reported here are similar to those in healthy volunteers in another study with the voxel placed in the ventral anterior cingulate, 2 and are slightly lower than the mean GSH levels from the dorsomedial prefrontal cortex in healthy controls 29 or from the left anterior cingulate in healthy controls. 21 When calculated relative to total creatine, GSH/tCr levels in this study were similar to or slightly higher than healthy control GSH/tCr levels measured using SPECIAL from the medial prefrontal cortex.…”
Section: Discussionsupporting
confidence: 74%
“…Accumulating in vivo evidence indicates that NAC administration can exert positive effects on glutamatergic neurotransmission via NAC-induced stimulation of the cysteine-glutamate antiporter (system x c − ) in glial cells (Durieux et al, 2015; Kupchik et al, 2012). Increased glutamate levels in the extra-synaptic space activates presynaptic mGluR2/3, which results in the inhibition of glutamate release into the synaptic cleft thereby mitigating the development of glutamate excitotoxicity (Dean et al, 2011; Kupchik et al, 2012).…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%
“…As apart from GSH, other important brain metabolites were to be detected and quantified in our study; we used short-TE PRESS (echo time-point-resolved spectroscopy) for good overall signal-to-noise ratio (SNR) and acceptable scan durations. Short-TE PRESS has been validated for GSH quantification with phantom experiments by others [ 23 ] and has been applied in clinical studies for voxel locations, which are similar to ours [ 24 ] or closer to the sinuses and thus even more challenging in terms of spectral quality [ 23 ]. MEGA-PRESS (Meshcher Garwood-PRESS), which has been established as a gold standard for GABA detection, has also been proposed for GSH editing.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study analyzing GSH concentrations in ASD has been published to date. Durieux et al [ 24 ] found no GSH signal differences between male ASD patients and age- and IQ-matched controls in the basal ganglia and the dorsomedial prefrontal cortex (DMPFC). Several schizophrenia studies have been performed with mixed results: In the largest study in first-episode schizophrenic patients, 22% higher medial temporal lobe GSH concentrations were found compared to the control group [ 27 ].…”
Section: Introductionmentioning
confidence: 99%